6-weekly bevacizumab versus 4-weekly ranibizumab for neovascular age-related macular degeneration： a 2-year outcome - Chiam, Patrick J; Ho, Vivian W; Hickley, Nicholas M; Kotamarthi, Venkat (International journal of ophthalmology, 2016)
AIM： To compare visual acuity and central macular thickness（CMT） changes in neovascular age-related macular degeneration patients treated with either 6weekly bevacizumab regimen or 4 weekly ranibizumab on an as required basis.·METHODS： Patients made an informed choice between bevacizumab 1.25 mg or ranibizumab 0.5 mg. The selected treatment was administered in the first 3 visits.Bevacizumab patients were followed-up 6 weekly and ranibizumab 4 weekly. Retreatment criteria was based on the reduction of 〉5 letters in the best-corrected visual acuity（BCVA）, the presence of retinal fluid on optical coherence tomography（OCT） or new retinal haemorrhage.·RESULTS： Visual acuity at 2y bevacizumab patients gained 7. 0 letters and ranibizumab 9. 2（ P = 0. 31, 95 %CI-6.4 to 2.0）. At 2y 86% of bevacizumab and 94%ranibizumab patients had not lost 15 letters or more（P =0.13）. Mean CMT decreased at 2y bevacizumab by 146 μm,ranibizumab 160 μm（P =0.72）. Mean number of injections was at 2y bevacizumzb 11.9, ranibizumab 10.3（P =0.023）.· CONCLUSION： Bevacizumab 6 weekly on an as required basis was not demonstrably non-inferior to ranibizumab 4 weekly pro re nata（prn） in terms of BCVA and change in CMT. In the bevacizumab group, one more injection was required in the second year compared to the ranibizumab group.